Külək turbinlərinin modelləşdirilməsi və dizaynı - Xəlilov, Səbuhi; Cavadov, Əmrah (My University, 2024)
Wind energy is today the fastest-growing area among alternative energy sources. Over the past twenty years, this area has turned from an exotic phenomenon into a rapidly developing direction, where more efficient and reliable technologies have been developed, the cost of which has almost halved in ten years, allowing them to be established for commercial production. A modern wind turbine can produce 180 times more electricity than 20 years ago, and the price of equipment (kWh) has more than halved over these years. Thanks to rapidly developing technologies and increasing productivity, the overall cost of wind energy continues to decrease. Moreover, the formation of wind energy as an independent sector has a positive effect on the economic development of modern society.
Modeling and design of wind turbines
Keywords: Wind energy potential; Wind generator